Comparative Analysis of the U.S. and Armenian Veteran Mental Health Services - Asriyan, Elina; Gevorgyan, Davit; Mesrobyan, Lilit; Naghdalyan, Mher (Տիգրան Մեծ)
This article aims to present the analysis of system-atic approaches to the treatment of PTSD and war-related mental health issues adopted in Armenia and to illuminate possible differences and similarities between the latter and the best practices implemented in the USA. The analysis of the aforementioned mental health systems has been carried out based on three main axes: general treatment management, diagnosis and treatment planning, treatment and subsequent follow-up.As a result, we have concluded that despite the absence of a regulatory framework of the Armenian mental health sys-tem and the lack of a well-thought-out organization of patient admission, therapy and follow-up procedure, the model in place has more similarities than differences with the U.S. sys-tem. In particular, the therapeutic modalities, the format of psychotherapy, and the clinical supervision of specialists im-plemented in the psychological centres across Armenia are in line with U.S. standards. Nevertheless, as the psychological assistance delivered to veterans is not regulated on a national level and as there is currently a significant lack of institutional and professional resources, the improvement of the efficiency and the quality of mental health services in Armenia remains an important challenge.
Keywords: Social philosophy